PERAN MEDIA AUDIOVISUAL DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DI SDI PERAWAEA - Coo, Maria Goreti (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to assess students' understanding in Catholic Religious Education using audiovisual media at Sekolah Dasar Inpres Perawea. The research also seeks to optimize the use of audiovisual media in enhancing students' knowledge of Catholicism and improving teachers' professionalism in delivering effective and efficient lessons. The research employed a quantitative method with an experimental design. Data were collected through comprehension tests, observations, and interviews, and were analyzed statistically. The findings indicate that the use of audiovisual media significantly enhances students' comprehension of the Catholic Religious Education material. Students who learned with audiovisual media demonstrated higher absorption of the subject matter compared to those who learned without it. Additionally, the use of audiovisual media helped teachers present complex material more clearly and engagingly, thus supporting the achievement of educational goals more effectively. In conclusion, audiovisual media is an effective tool for improving students' understanding of Catholic Religious Education at Sekolah Dasar Inpres Perawea. The use of this media not only benefits students but also enhances teachers' professionalism in teaching. Therefore, optimizing the use of audiovisual media in the classroom is recommended to improve the quality of education at the school.